Growth performance, microbial and hemato-biochemical profile, and organs histology of broiler chickens fed diets supplemented with a seasoning named Jumbo Cube as source of monosodium glutamate - Azine, Pascaline Ciza; Kana, Jean Raphaël; Ngouana, Tadjong Ruben; Kenfack, Audrey; Sonkeng, Nzako Aurelie; Bunto, Kemajou Quentin; Djemen, Tchantchou Chamberlain; Lyale, Simo Philippe; Kemmo, Kenhagho Arielle; Ngnouamen, Nia Tatiana; et al. (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: this study was conducted in order to assess the effects of dietary Jumbo Cube as source of Monosodium Glutamate (MSG) on production performances of broiler chickens. Materials and methods: 320 day-old Ross 308 broiler chicks were randomly divided into five groups of 64 chicks each. Negative and positive control groups were fed on basal diet with no supplement (R0-) and 1 gm of antibiotic (R0+) respectively and the 3 others groups were fed on diets supplemented with the quantities of Jumbo cube containing 1 mg, 2 mg and 4 mg of MSG/Kg of feed. Feed intake (FI), feed conversion ratio (FCR), weight gain (WG), blood parameters and intestinal microbial counts were evaluated. Results: Results revealed that feeding broilers with Jumbo Cube as MSG source significantly (P<0.05) decreased FI at the starter phase with no significant effect at the finisher phase. Diet supplemented with 2 mg of MSG/Kg significantly (P<0.05) increased LBW and WG, and decreased FCR. Dietary MSG significantly (P<0.05) has no significant effect on bacteria counts during starter phase. At the finisher phase, GMS induced a significant increase in lactic bacteria and E. coli counts as compared to the control ration without any supplement. White blood cells (WBC) significantly decreased with inclusion of 1mg and 2 mg of MSG/Kg. Dietary MSG markedly decreased albumin/globulin ratio, LDL-cholesterol and creatinine. Conclusion: It was concluded that Jumbo Cube can be used as source of MSG (2 mg/Kg) to improve growth performance in broiler chickens. http://doi.org/10.5455/javar.2018.e258